Literature on education and technology under Paulo Freire’s framework: a portrait and a critical cutoff (Práxis Educativa, 2021)
The article presents an approximate portrait of works on education and technology in Brazil that claimed themselves as being developed under Paulo Freire’s framework. The composition performed through content analysis exposes characteristics of the sample of 29 articles. The investigation focused on one point of this portrait, when analyzing whether the works addressed the relations of power, exploitation and domination, common elements in critical approaches and examined through the contributions of Apple and Au (2015) and Selwyn (2016a, 2017), in dialogue with Freire (1987, 1998). Although they do not adhere to the predominant discourse in the literature in the area, most articles do not explore these important issues for a critical approach. In the limits of this research, it is highlighted the necessity of more works of education and technology under Paulo Freire’s framework that considers the political nature of technology.Keywords: Paulo Freire. Education. Technologies.